The church in mission in the wake of emerging indigenous religious trends in South Africa - Tau, Resemate Klaas (University of the Free State, 2007)
South Africa is characterised by breath-taking developments in all its major spheres of life, social, political, economic, cultural and religious, etc. After some decades of colonial rule, inter-racial strife and polarisation between races, South Africa prides herself in a "peaceful transition" from colonial and Apartheid rule to constitutional democracy ushered in during 1994. The success of South Africans in handling their multi-cultural diversity has made South Africa the primary object of world attention, a microcosm and a mirror image of the world itself. South Africa has correctly been described as "a world in one country" and a "rainbow nation". However, recently, and just before and shortly after gaining freedom from its colonial and Apartheid past, indigenous religions in South Africa have re-emerged on the scene. They are highly critical of Christians in South Africa, and seem to delight in pointing out its failures during colonialism and the Apartheid era. They contest the Christian claim to uniqueness and final truth and also the right of Christians to convert others to their faith. They claim universal validity for themselves. They invite the Church to compromise and to cooperate. In spite of all the outer show of resurgence by the indigenous religions, there is evidence of a growing spiritual vacuum in certain areas of our country. This is evidenced by increasing moral decay in the society, which prompted the government to launch the Moral Regeneration Movement. This study examines the role of the Church in the wake of emerging indigenous religious trends in South Africa. It seeks to discover how the Church in Mission could, in the wake of emerging indigenous religious trends, order its life and practices in order to give positive witness to indigenous people in South Africa. It seeks to explore whether elements of emerging indigenous religious trends in South Africa afforded the Church an opportunity to recoil under the glaring failures of the past or an alternative opportunity of declaring its faith. It argues that the Church has a critical role to play in South Africa only if it would strongly renew itself and engage in mission. Practical means of social involvement are given prominence in this study.

Suid-Afrika word op alle belangrike lewensterreine, soos die sosiale, politieke, ekonomiese, kulturele en godsdienstige terreine, deur asemrowende ontwikkelings gekenmerk. Suid-Afrika kan na 'n aantal dekades van koloniale oorheersing, rassewrywing en rassepolarisasie met reg trots voel op die "vredesame oorgang" vanaf die koloniale en Apartheidsregering na 'n konstitusionele demokrasie wat in 1994 van stapel gestuur is. Die sukses wat Suid-Afrikaners met die hantering van hulle multikulturele verskeidenheid gehad het, het Suid-Afrika in die middelpunt van die wêreld se belangstelling geplaas, 'n mikrokosmos en 'n spieëlbeeld van die wêreld self. [nheemse godsdienste het egter onlangs, net vóór en ná vryheid van die koloniale en Apartheidsverlede verkry is, weer op die toneel verskyn. Hulle staan baie krities teenoor Christene in Suid-Afrika en put skynbare genot daaruit om die Christendom se mislukking tydens kolonialisme en die Apartheidsera uit te wys. Hulle betwis Christene se aansprake op uniekheid en die finale waarheid, asook Christene se reg om andere tot hulle geloof te bekeer. Hulle eis vir hulleself universele geldigheid op. Hulle nooi die Kerk uit om kompromieë aan te gaan en met hulle saam te werk. Daar is ten spyte van die uiterlike vertoon van 'n opbloei onder inheemse godsdienste getuienis van 'n toenemende geestelike lugleegte in sekere dele van ons land. Dit word aangedui deur 'n toenemende morele verval in die samelewing, wat die regering daartoe genoop het om die Morele Herbewapeningsbeweging te loods. Hierdie studie ondersoek die Kerk se rol in die lig van opkomende inheemse godsdiensstrominge in Suid-Afrika. Dit probeer agterkom hoe die missionêre Kerk in die lig van opkomende inheemse godsdiensstrominge haar lewe en praktyke behoort te orden ten einde vir die inheemse mense in Suid-Afrika tot 'n positiewe getuienis te wees. Dit probeer verder agterkom of elemente van die opkomende inheemse godsdiensstrominge in Suid-Afrika die Kerk daartoe bring om as gevolg van mislukkings in die verlede terug te deins en of die Kerk dit as nog 'n geleentheid kan beskou om haar geloof te bely. Die studie argumenteer dat die Kerk slegs 'n rol in Suid-Afrika te speel het as dit sigself deeglik vernuwe en by sending betrokke raak. Hierdie studie stel praktiese maniere om sosiaal betrokke te raak, voorop.
Thesis (Ph.D. (Missiology))--University of the Free State, 2007
Keywords: Africanisation; Globalisation; Culture; Mission; Conformity; Witnessing; Nature of the church; Contextualisation; Christianity and culture; Christianity and other religions; Indigenous peoples -- Religion; African traditional religion